111 Add a filter or send a tweet? Differences in social media use between staff targeted and student targeted great ormond street conferences. (15th December 2021) - Tutt, Abbie; Olariu, Adina; Trecchi, Nadia; Willock, Marissa; Poisson, Jeroen; Brown, Shereen; Stow, Peter; Poisson, Justin; Smith, Jonathan; Blackburn, Simon; Costa, Cristine Sortica da; Wheeler, Olivia
Abstract : Background: Social Media is an accompanying staple to conferences, and it has slowly become more common to see conferences encouraging interaction online as well as in person. We compare two conferences run by GOSH PGME (Summer School for Students and the Staff Conference) to examine if there are differences in the way social media is used between students and staff of GOSH. Methods: Two of GOSH PGME's social accounts were used to accompany the virtual conferences; Twitter: @GOSHPGME and Instagram: @pgme.education. We looked at GOSH Summer School and GOSH Conference, both in 2020. The statistical social media data was gathered from both accounts across the days of the conferences and compared to establish if there were any differences in of use of the platform. Results: The average figures of the GOSH Summer School across the four days were used, as the GOSH Conference was a one-day conference. GOSH Summer School attracted 10, 165 impressions, 103.3 likes and 68 profiles visits on Twitter and 10.038 Impressions, 107 likes and 6612 profile visits on Instagram. The GOSH Conferences had 19, 692 impressions, 198 likes and 57 profile visits on Twitter and 4269 Impressions, 79 likes and 107 profile visits on Instagram. Discussion: The engagement statistics and broad use of social media to compliment the two conferences show how social media can be used to target specific audiences. There is a difference in the platforms favoured by staff and students. Staff engaged more with Twitter, whereas students preferred Instagram. However, Twitter had the greater outreach across the two conferences, reaching more users than Instagram. This data shows that targeted social media approaches should differ between staff and student populations to maximize engagement and interaction with conferences